Radiation measurement from mobile base stations at a university campus in Malaysia - Islam, Md. Rafiqul; Khalifa, Othman Omran; Ali, Liakot; Azli, Amir; -, Mohd Zulkarnain (Science Publications, 2006)
The tremendous growth of telecommunication industry results the number of hand phone users increases everyday. In order to support the growing number of users, the mobile base stations can be seen in almost everywhere. This scenario has created uncomfortable feelings to the people that they may be affected by the radiations from antennas. A measurement was done at student hostels and office premises near to base stations in International Islamic University Malaysia, Gombak campus. Measured values are compared with Malaysian Communication and Multimedia Commission (MCMC), IEEE and ANSI recommendations for safety guidelines. The results are presented in this study.